If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-7-8x=13+4x-3x
We move all terms to the left:
5x-7-8x-(13+4x-3x)=0
We add all the numbers together, and all the variables
5x-8x-(x+13)-7=0
We add all the numbers together, and all the variables
-3x-(x+13)-7=0
We get rid of parentheses
-3x-x-13-7=0
We add all the numbers together, and all the variables
-4x-20=0
We move all terms containing x to the left, all other terms to the right
-4x=20
x=20/-4
x=-5
| 5y-(-13)=12 | | 28=3x^2-5x | | X-9=1-x | | 5b-+12=43 | | 7-6m=-8m+1 | | 2x-4=5x-27 | | (3x)+(2x-19)+(4x+10)=180 | | 4x-3x+3=16 | | 5p-9=2p=12p | | -5x-8.6=-15x-8.6 | | 4w+20=1w+26 | | 7/m=6/10 | | |3x+7|=2*|x-6| | | 2x+3=4x-10 | | -6(2x+5)=2/3x | | 3m+4(8m+6)=-18-7m | | 2/3x-1.3=1/4x | | 2x*2-3x-2=0 | | 2(3y+9)=24 | | 4½+q=9½ | | (2n+12)+(3n-7)=90 | | 2x2−3x−2=0 | | 4-7x=-66 | | 3(v+2)=-2v+1 | | 2/3x=10/9 | | x=3(5)+1/2102 | | √3x+10=x+4 | | -60=6x-2 | | 5y+5=9y-15 | | -23x+7=-3 | | -7=12+x/4 | | 2y2-y-6=0 |